Right Ventricular Myocardial Stiffness in Experimental Pulmonary Arterial Hypertension: Relative Contribution of Fibrosis and Myofibril Stiffness - Rain, Silvia (Circ Heart Fail, 2016)
BACKGROUND—: The purpose of this study was to determine the relative contribution of fibrosis-mediated and myofibril-mediated stiffness in rats with mild and severe right ventricular (RV) dysfunction. METHODS AND RESULTS—: By performing pulmonary artery banding of different diameters for 7 weeks, mild RV dysfunction (Ø=0.6 mm) and severe RV dysfunction (Ø=0.5 mm) were induced in rats. The relative contribution of fibrosis- and myofibril-mediated RV stiffness was determined in RV trabecular strips. Total myocardial stiffness was increased in trabeculae from both mild and severe RV dysfunction in comparison to controls. In severe RV dysfunction, increased RV myocardial stiffness was explained by both increased fibrosis-mediated stiffness and increased myofibril-mediated stiffness, whereas in mild RV dysfunction, only myofibril-mediated stiffness was increased in comparison to control. Histological analyses revealed that RV fibrosis gradually increased with severity of RV dysfunction, whereas the ratio of collagen I/III expression was only elevated in severe RV dysfunction. Stiffness measurements in single membrane-permeabilized RV cardiomyocytes demonstrated a gradual increase in RV myofibril stiffness, which was partially restored by protein kinase A in both mild and severe RV dysfunction. Increased expression of compliant titin isoforms was observed only in mild RV dysfunction, whereas titin phosphorylation was reduced in both mild and severe RV dysfunction. CONCLUSIONS—: RV myocardial stiffness is increased in rats with mild and severe RV dysfunction. In mild RV dysfunction, stiffness is mainly determined by increased myofibril stiffness. In severe RV dysfunction, both myofibril- and fibrosis-mediated stiffness contribute to increased RV myocardial stiffness.